RESEARCH OF PROFESSIONAL PREPARATION FOR FUTURE STUDENTS MANAGERS - Іваненко, Н.; Оргєєва, С.; Харун, О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article analyzes the literature, which convinces that the professional training of stewards is in need of a more detailed study of this problem. It was found out that steward managers are representatives of the profession "person-man", the peculiarities of which professional activity has the following typical characteristics of professional knowledge, abilities and skills, and also this profession is characterized by intense mental labor, abnormal working hours; requires the mobility of the motor, visual, auditory analyzers, the tension of thinking, will and attention. The basis of successful professional training is the potential of the steward manager, his professional and organizational knowledge, life wisdom, ability, intelligence, authority, intellectual development, imagination, leadership ability, motivation, courage, intuition, self-confidence, ability to choose opportunities, a sense of justice , tolerance, mental and physical health, etc. At the same time, attention is drawn to the fact that the manager-steward will not achieve the wide-ranging knowledge, experience and development without such features as intelligence, creativity, and analytical thinking skills. In addition, on the basis of a systematic approach in the article the program of professional training of future steward managers is considered through the creation of the appropriate condition. The content of the training program of stewardship managers, the strategy of priority areas and its improvement depends on many socio-economic factors. It has been established that an important feature is the development and implementation of a stewardship training program that can improve the level of security at the stadium and the effectiveness of providing services to visitors. It is proved that the process of professional training of steward managers will be more effective if the theoretical and methodological principles of the corresponding direction will be built on the mastery of certain qualities aimed specifically for this profession, and the technologies of their implementation are oriented on the construction of individual trajectories of stewards management development, their self-realization and self improvement.